Energy-Water-Environment Nexus and the Transition Towards a Circular Economy: The Case of Qatar - Abdul-Jalil Ibrahim (14158983) (2022)
Background Qatar’s per capita consumption of both energy and water is among the highest in the world. Documentation of methods to reduce energy and water use and its impact on the environment is crucial. A circular economy (CE) ensures that economic growth must not necessarily lead to more resource consumption. Materials and methods This study aims to discuss the CE approach with a focus on understanding the interdependencies between energy and water and their impact on the environment. The study explores the energy-water-environment nexus and how Qatar can leverage this to transition to a CE. The policy landscape and strategies related to energy and water use sectors are presented, addressing efficiencies and substitutes from a circular economic viewpoint. Results The findings show that electricity and mobility sectors(energy perspective of the CE) and agriculture and water supply system (water perspective of the CE) of the Qatari economy provide an opportunity for regeneration, virtualising, exchanging, optimising, sharing and closing loops to achieve CE growth. Conclusions The nexus between the mobility, electricity, agriculture and water supply system needs consideration for optimal policy outcome for the CE in Qatar. The study recommends a need to embark on public awareness on moving away from linear economic to the circular economic paradigm and developing a comprehensive policy on Qatar’s circular economic approach that consolidates the Qatar National Vision 2030 and the National Development Strategy 2018–2022 to provide policy clarity and communication towards CE. Other Information Published in: Circular Economy and Sustainability License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s43615-021-00037-w